The psychosocial impacts of slow onset climate change events among youth in LMICs: A rapid evidence review - Clara Marty; Samy Amghar; Andrés Barrera Patlan; Alayne Adams (The Journal of Climate Change and Health)
Introduction: Recent research has sought to understand the complex experiences of climate change distress, which are highly prevalent among youth and in low- and middle-income countries (LMICs). However, most studies have focused on acute climate disasters and clinically diagnosable psychological responses, leaving a gap in understanding about how gradual climate change events impact broader psychosocial health. Methods: This review examined how slow-onset events relate to psychosocial distress among youth in climate-vulnerable LMICs using the PRISMA Rapid Review methodology. Four databases were searched, namely Scopus, Web of Science, MEDLINE, and Cochrane. Results: The initial search yielded 853 results, of which 14 articles met the inclusion criteria for data extraction and analysis, which employed a framework synthesis approach. Studies identified direct impacts of slow onset events (e.g., changing precipitation patterns), as well as indirect impacts on communities (e.g., housing instability) and resources (e.g., loss of livestock). These disruptions are often compounded by pre-existing vulnerabilities such as public debt and inadequate basic services. Faced by these challenges, youth employed many coping strategies such as religion and meaning-focused coping, to help minimize psychosocial distress. Psychosocial responses varied from feelings of worry and numbness to severe outcomes like suicidal ideation. Conclusion: This review reveals the diversified experiences of climate change, which are closely tied to social and community contexts. A robust research agenda on the psychosocial effects of slow-onset environmental changes is vital to better understand and mitigate its long-term mental health impact on youth.